(untitled) (International Journal of Engineering and Computer Science, 2016)
Switching techniques defines when and how packets/messages are forwarded through the network. The aim of the paper is to evaluate and establish a comprehensive view of different switching techniques. The main objective of the paper is to bring out the drawbacks and possible solutions to tackle them. Different switching techniques are used in different networks, each having its own advantage and disadvantage. Networking is a crucial area of research and a lot development has been made. We do not mean to give complete solutions to the disadvantages of different switching techniques, rather we intended to show an overview of all switching techniques along with their disadvantages